The Impact of Endurance Running Training on the Lipid Profile in Professional and Amateur Athletes: A Comprehensive Review - Zarzycki, Adam; Nowak, Dominika; Próchnicka, Magdalena; Siwek, Michał; Hamouta, Jakub; Długosz, Patrycja; Konat, Julia; Doroszuk, Wiktor; Noskowicz, Jan; Urban, Jan (Quality in Sport, 2025)
Endurance running is one of the most popular forms of physical activity, influencing many aspects of health, including lipid metabolism. Regular endurance exercise positively affects the lipid profile, which plays a key role in preventing cardiovascular diseases (CVD). Dyslipidemia, characterized by abnormal levels of cholesterol and triglycerides, is a significant risk factor for the development of these diseases. The purpose of this study is to analyze the impact of endurance running on the lipid profile of amateur and professional athletes, considering the differences in metabolic adaptations resulting from training intensity and lifestyle. A review of the available literature was conducted by searching official databases such as Pubmed and Google Scholar using the following keywords: dyslipidemia, endurance running, cardiovascular, lipoprotein lipase. The results indicate that regular endurance running enhances LPL activity, fatty acid oxidation, and cholesterol transport. Both moderate and high-intensity training lower LDL-C and triglycerides, while raising HDL-C. Lipid responses vary between amateur and professional athletes due to differences in training and lifestyle. Overall, endurance running with a healthy lifestyle effectively improves lipid profiles and reduces cardiovascular risk.